2018
DOI: 10.1123/jcsp.2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Essentials for Best Practice: Treatment Approaches for Athletes With Eating Disorders

Abstract: Eating disorders (EDs) and disordered-eating behaviors (DEBs), pose a high risk of morbidity and mortality, threatening physical health, emotional health, and overall quality of life. Unfortunately, among athletes, prevalence rates continue to increase. This document summarizes the challenges of establishing and navigating the multidisciplinary care needed to effectively treat EDs and DEBs among athletes. The benefits of timely and frequent communication within the multidisciplinary treatment team (MDTT) are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Eating disorders (EDs) are common and potentially serious conditions that have devastating effects on physical/emotional health, sports performance, and overall quality of life, carrying an increased risk of morbidity and mortality [ 1 , 2 ]. The Diagnostic and Statistical Manual of Mental Disorders (DSM-5) categorizes EDs into several specific types, including: Anorexia Nervosa (AN), Bulimia Nervosa (BN), Binge Eating Disorder (BED) Pica, Rumination Disorder, Avoidant/Restrictive Food Intake Disorder (ARFID), Other Specified Feeding or Eating Disorder (OSFED), Other Specified Feeding or Eating Disorder (OSFED), and Unspecified Feeding or Eating Disorder (UFED) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eating disorders (EDs) are common and potentially serious conditions that have devastating effects on physical/emotional health, sports performance, and overall quality of life, carrying an increased risk of morbidity and mortality [ 1 , 2 ]. The Diagnostic and Statistical Manual of Mental Disorders (DSM-5) categorizes EDs into several specific types, including: Anorexia Nervosa (AN), Bulimia Nervosa (BN), Binge Eating Disorder (BED) Pica, Rumination Disorder, Avoidant/Restrictive Food Intake Disorder (ARFID), Other Specified Feeding or Eating Disorder (OSFED), Other Specified Feeding or Eating Disorder (OSFED), and Unspecified Feeding or Eating Disorder (UFED) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results highlight that athletes’ disordered eating behaviour can precursor eating disorder symptoms. Therefore we recommend that not only coaches but also athletes, parents, and relevant personnel (e.g., physicians, physiotherapists, teachers) should be made aware of the symptoms of disordered eating (i.e., regular use of unhealthy weight control methods) and that it is a warning sign that should not be taken lightly or ignored [25, 26]. 33% of participants use at least one weight control method regularly, and athletes use up to six weight control methods at the same time, which both can be described as disordered eating [5, 7, 8, 9, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, particularly coaches should be aware of the potential consequences when making comments that suggest an association between leanness/thinness and performance (i.e., athletes use methods to lose weight fast). Instead, coaches should educate athletes about the negative short- and long-term psychological and physiological consequences of fast and unhealthy weight loss and give appropriate advice for healthy dieting or refer athletes to an expert [9, 25, 26]. Results also indicated that athletes’ attitudes and expectations regarding an ideal body are modeled by friends and team norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing knowledge of professionals with responsibilities for athletes in taekwon-do may also be important so that they can recognise those athletes at risk from eating disorders and provide the necessary skills to either support them or signpost them on to a mental health care provider. A coach or trainer who is eating disordered informed or certified is better able to detect and support the recovery of athletes with eating disorders (Conviser et al, 2018).…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%